2007
DOI: 10.1190/1.2732550
|View full text |Cite
|
Sign up to set email alerts
|

Model reliability for 3D electrical resistivity tomography: Application of the volume of investigation index to a time-lapse monitoring experiment

Abstract: Solution appraisal is difficult for large 3D, nonlinear inverse problems such as electrical resistivity tomography (ERT). We construct the volume of investigation index (VOI) as the sensitivity of the inversion result to a variable-reference model. This limited exploration of the model space provides an efficient and pragmatic method of appraisal for a particular data set and a 3D model domain. We present a synthetic example to demonstrate the applicability of the VOI as a tool for characterizing model reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 23 publications
5
33
1
1
Order By: Relevance
“…This similarity reflects the reliability of the applied techniques. A comparison with published results (e.g., [34]) shows that the vertical configurations reflect better resolution (of lower ROI values) than the lateral ones which confirms the results obtained here.…”
Section: Evaluation Of Reconstructed Tomogramssupporting
confidence: 80%
See 2 more Smart Citations
“…This similarity reflects the reliability of the applied techniques. A comparison with published results (e.g., [34]) shows that the vertical configurations reflect better resolution (of lower ROI values) than the lateral ones which confirms the results obtained here.…”
Section: Evaluation Of Reconstructed Tomogramssupporting
confidence: 80%
“…However, their filtered data sets after removing this noise can resolve well the subsurface targets of CO 2 plume, reservoir, and cap rock assuming enough coverage of more than one electrode spacing. These conclusions are in accordance with that of, for example, Oldenburg and Li [16] and Oldenborger et al [34] and opposed to that of Zhou and Greenhalgh [23]. In solute transport experiments, the former authors found that the vertical βvcs tomograms show more reliable subsurface structures than the horizontal β tomograms.…”
Section: Effect Of Configurations and Model Scenariossupporting
confidence: 76%
See 1 more Smart Citation
“…The images indicate thin alternating resistive and conductive layers, possibly underlain by conductive bedrock at ~8 m bgl. Two of these three resistive layers do not appear to be continuous, although their disappearance with increasing distance from the borehole electrodes is probably due to the associated decrease in image resolution with increasing distance (Kemna et al, 2002, Oldenborger et al, 2007b. It is possible that the lack of quantitative agreement between the logs and the images below 6 m bgl is due to slippage in the core barrel.…”
Section: Ground Truth and Baseline Resistivity Imagementioning
confidence: 80%
“…Optimal experimental and data processing designs may be used to improve these uncertainties. Optimal design theory is applied to both linear and nonlinear geophysical problems (Curtis, 2004a,b) such as seismic tomography (Curtis, 1999a,b;Maurer et al, 2009;Ajo-Franklin, 2009), amplitude variation with offset/angle survey and processing (van den Berg et al, 2003;Coles and Curtis, 2010;Guest and Curtis, 2009, 2011) earthquake or microcosmic location surveys (Curtis et al, 2004;Winterfors and Curtis, 2008) and electric and electromagnetic surveys (Maurer and Boerner, 1998;Maurer et al, 2000;Stummer et al, 2002aStummer et al, ,b, 2004Oldenborger et al, 2007). A review of the recent advances in survey design is given in Maurer et al (2010).…”
Section: Introductionmentioning
confidence: 98%